The wellness economy: A comprehensive system of national accounts approach - Rafael Martin M. Consing; Michael John M. Barsabal; Julian Thomas B. Alvarez; Mahinthan J. Mariasingham (Asian Development Bank (ADB), 2020)
This paper provides a comprehensive discussion on different, interconnected methods of using the system of national accounts to measure the relevance of a country's wellness sector to its overall economy. Procedures are discussed for using input-output analysis to derive the production and employment linkages between wellness and nonwellness sectors. We also discuss procedures for using the hypothetical extraction method to derive and decompose the production and employment losses that may arise when a country's wellness sector is removed from the economy. These procedures are then used to provide estimates for ten countries in developing Asia across two time periods which together provide a proxy for the region (Asia-10), along with a discussion on how these wellness economies have grown and how each one's labor productivity and wellness sector structure have evolved between the two periods.
Keywords: E01; C67; D57; I39; R15; 330; economy; employment; input-output; national accounts; wellness